2004
DOI: 10.1093/sw/49.2.231
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Investigation of Adherence Issues for Men Who Are HIV Positive

Abstract: People who are HIV-positive and people who have been diagnosed with AIDS have new hope in the form of antiretroviral medications. However, many social workers remain unaware of the rigors of this treatment regimen and the difficulties it presents. This article presents the results of a qualitative study of HIV-positive individuals who have struggled with the adherence issues endemic to antiretroviral treatment and seeks to give voice to their experiences. The article seeks to educate social workers about antir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 7 publications
2
10
0
2
Order By: Relevance
“…This is consistent with previous studies by Metsch, Pereyra, & Brewer (2001), Westerfelt (2004), and by Conway (2007) that showed that HIV/AIDS patients may miss treatment due to these reasons. Taking HAART may be at the top of one's priorities but, because patient's may be anxious about the availability of money to buy daily necessities, and their access to food, they may end up procrastinating, being distracted or being busy either looking for food or money, or going to work so they can get paid, and may end up forgetting to take HAART altogether.…”
Section: Not Caring Procrastination or Being Too Busysupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous studies by Metsch, Pereyra, & Brewer (2001), Westerfelt (2004), and by Conway (2007) that showed that HIV/AIDS patients may miss treatment due to these reasons. Taking HAART may be at the top of one's priorities but, because patient's may be anxious about the availability of money to buy daily necessities, and their access to food, they may end up procrastinating, being distracted or being busy either looking for food or money, or going to work so they can get paid, and may end up forgetting to take HAART altogether.…”
Section: Not Caring Procrastination or Being Too Busysupporting
confidence: 93%
“…Studies indicate that procrastination and being too distracted or busy can lead to low HAART adherence (Hill, Kendall, & Fernandez, 2003;Powell-Cope et al, 2003;Westerfelt, 2004). One may procrastinate or be too busy or distracted due to work and/ or because they are searching for money to buy daily needs, among other reasons.…”
Section: Procrastination and Being Too Distracted Or Busymentioning
confidence: 99%
“…However, even though observations only lasted half a day to one day, there were very few indicators that the observed consultations were not "typical." Another limitation is the non-inclusion of patient's viewpoints, although our findings are supported by others who have interviewed patients [33-40]. …”
Section: Discussionsupporting
confidence: 57%
“…These issues have been described in the literature from the developed world (Abel & Painter, 2003; Hill et al, 2003; Remien et al, 2003; Westerfelt, 2004; Wood et al, 2004), including among IDUs (Witteveen & van Ameijden, 2002), but little has been published from developing countries. However, several studies have reported on the connection between depression and HIV status in African and Asian populations (Kaharuza et al, 2006; Mills et al, 2006; Ross et al, 2007; Sahay et al, 2007; Simbayi et al, 2007) as well as in China (Jin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%